مسئولية الحكومات في مواجهة زنا المحارم دراسة فقهية - Ibrahim Mohamed, Hossam El Din (IIUM Press, International Islamic University Malaysia, 2015)
زنا المحارم، سفاح الأقارب، قضايا الشرف، كلها مسميات لظاهرة واحدة تفشت في مجتمعاتنا العربية والإسلامية، وأخذت تستعر نارها، في تعتيم عليها من قبل الأسرة، وبسبب ضعف الإيمان وانحلال الأخلاق، يضاف لذلك إهمال الحكومة من القيام بدور المنوط بها، وتقاعسها عن القيام بواجباتها تجاه مواطنيها، هذه الدراسة تلقي الضوء على هذه الجريمة التي استفحلت في المجتمع، مهددةً كيان الأسرة المسلمة، بالتفسخ والانهيار، فمن خلال هذا البحث تم التعريف بهذه الجريمة البشعة وبأدلة تحريمها، والتي حرمتها الشريعة ، والتي نصت على قتل مرتكبها شرعاً، كما أوضحت صور إهمال الحكومة عن القيام بواجباتها والتي تعتبر هي الأسباب الرئيسة لهذه الجريمة ومن أهمها: عدم توفر المسكن المناسب، والبطالة والفقر، وعدم ضبط ومراقبة الإعلام المشاهد والمسموع والمقروء، وعدم سن التشريعات القانونية الزاجرة التي تتناسب وبشاعة هذه الجريمة، وكذلك دور الأهل في هذه الجريمة من ضعف الإيمان، والتبرج في اللباس، وقلة الوعي بالأسباب المؤدية لهذه الجريمة وتلافيها، ثم دراسة أهم السبل والوسائل للحد من هذه الظاهرة وصولاً للقضاء عليها، ويختتم البحث بنتائج وتوصيات مهمة. ******************************************************* Incest, incest, honor issues, all of the names and single phenomenon rampant in the Arab and Islamic societies, and took a raging fire of, the blackout by the family, and because of the weakness of faith and the dissolution of morals, add to that the neglect of the government to play a role assigned to it, and failing to carry out their duties to its citizens, this study sheds light on this crime that has taken hold in society, threatening the Muslim family entity, Baltvsch and collapse, as the picture the neglect of the government made it clear it is most important: the lack of adequate housing, unemployment, poverty, lack of control and monitor the media viewer, audio and reading, and the failure to enact legislation Legal Al'zajrh commensurate with the horror of this crime, and finery in dress, and lack of awareness of the reasons leading to this crime and to avoid them, and then study the most important ways and means to reduce this phenomenon down to eliminate them, and concludes with search results and recommendations of the task.